2016
DOI: 10.2337/dc16-0843
|View full text |Cite
|
Sign up to set email alerts
|

APOE Genotypes Associate With Cognitive Performance but Not Cerebral Structure: Diabetes Heart Study MIND

Abstract: OBJECTIVEDementia is a debilitating illness with a disproportionate burden in patients with type 2 diabetes (T2D). Among the contributors, genetic variation at the apolipoprotein E locus (APOE) is posited to convey a strong effect. This study compared and contrasted the association of APOE with cognitive performance and cerebral structure in the setting of T2D.RESEARCH DESIGN AND METHODSEuropean Americans from the Diabetes Heart Study (DHS) MIND (n = 754) and African Americans from the African American (AA)-DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…It is unclear if e2 has a protective role on cognition of older adults. Older adults who are e2 carriers performed significantly better on cognitive domains pertaining to the frontal network (e.g., processing speed, attention, and executive functions) in some studies ( Sinclair et al, 2017 ), while the majority of findings did not find any significant associations with e2 or even demonstrated adverse effects on cognitive performance ( Greenwood et al, 2000 ; Bennett et al, 2009 ; Alfred et al, 2014 ; Marioni et al, 2016 ; Palmer Allred et al, 2016 ; Lancaster et al, 2017 ). Verbal fluency (phonemic and categorical), language, and visual-spatial functioning were not significantly associated with e2 in all studies that examined these domains.…”
Section: Cognitionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is unclear if e2 has a protective role on cognition of older adults. Older adults who are e2 carriers performed significantly better on cognitive domains pertaining to the frontal network (e.g., processing speed, attention, and executive functions) in some studies ( Sinclair et al, 2017 ), while the majority of findings did not find any significant associations with e2 or even demonstrated adverse effects on cognitive performance ( Greenwood et al, 2000 ; Bennett et al, 2009 ; Alfred et al, 2014 ; Marioni et al, 2016 ; Palmer Allred et al, 2016 ; Lancaster et al, 2017 ). Verbal fluency (phonemic and categorical), language, and visual-spatial functioning were not significantly associated with e2 in all studies that examined these domains.…”
Section: Cognitionmentioning
confidence: 92%
“…It is also postulated that the effect of e2 may be more prominent in old-older adults (≥75) ( Staehelin et al, 1999 ; Rajan et al, 2019 ) and in women ( Hyman et al, 1996 ; Davies et al, 2014 ; Shinohara et al, 2016b ). Whether there is a racial difference in the effect of e2 is inconclusive, as only three studies ( Blair et al, 2005 ; Palmer Allred et al, 2016 ; Rajan et al, 2019 ) included ethnically diverse samples and only one found a significantly smaller effect in African-Americans compared to Caucasian Americans ( Blair et al, 2005 ).…”
Section: Cognitionmentioning
confidence: 99%
“…Among those with mild cognitive impairment, APOE-ε4 alleles are more strongly associated with lower hippocampal volumes among women compared with men (35). However, the relationship between APOE genotype and cognition may be altered among individuals with T2DM, for example APOE-ε2 may not be protective (36).…”
Section: Independence Of Sex Differences From Risk Factor Imbalances and Subgroupingmentioning
confidence: 99%
“…2,3 The precise mechanisms by which T2DM increases the risk for AD are not fully understood, but substantial evidence links AD risk to insulin resistance and impaired insulin signaling in T2DM. 4 Apolipoprotein E (ApoE) genotype is the most consistently observed genetic contributor to late-onset AD. There are three alleles of ApoE gene, namely ε2, ε3, and ε4, which encode ApoE2, ApoE3, and ApoE4 protein, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…T2DM and AD share many pathophysiological features, such as insulin resistance, deregulated glucose metabolism, peripheral oxidative and inflammatory stress, amyloid aggregation, and neurodegeneration 2,3 . The precise mechanisms by which T2DM increases the risk for AD are not fully understood, but substantial evidence links AD risk to insulin resistance and impaired insulin signaling in T2DM 4 …”
Section: Introductionmentioning
confidence: 99%